Decoding digital competencies: a bibliometric analysis of academic librarianship - Sa’ari, Haziah; Sahak, Mohd Dasuki; Goulding, Anne (Penerbit UiTM Rembau, 2023)
As the digital revolution permeates academic librarianship, the salience of digital competencies has burgeoned. This bibliometric study embarks on an in-depth exploration of the sphere of digital competencies in academic librarianship from 2010 to 2023, with the purpose of understanding its evolutionary trajectory, unearthing emerging research pathways, and anticipating the progression of the field. Using a strict bibliometric analysis of 144 scholarly articles written during this time, the study gives a full picture of how pedagogical and digital skills work together to shape the future of this important field. It underscores the integral interrelationship amongst bibliometrics, scientometrics, and informetrics—tools that, despite their significance, receive scant acknowledgement in the realm of digital competencies for academic librarianship. This comprehensive analysis highlights the universal importance of digital competencies, underscoring significant contributions from both developed and developing nations while signaling the imperative for enhanced digital competencies, particularly in less developed regions. The study presents an array of digital competency themes, emphasizing the need for regular upskilling opportunities to keep pace with the dynamic nature of digital technologies, while underscoring the challenges posed by the ceaseless evolution of technology. It concludes with a call to action for the academic librarianship community to navigate this evolving paradigm with nuanced understanding, critical insight, and unwavering dedication, committing to continuous growth and innovation to secure their irreplaceable role in the digital age. Serving as a pioneering contribution, this study presents a wide-ranging analysis of the current trajectories and advancements in digital competencies for academic librarianship, delineating the pathway for subsequent academic investigations in this critical area of inquiry.